COVID-19 Trends in a Northeastern Brazilian State from the Start of the Pandemic: Exploring an Alternative Time Series Method - Matheus Paiva Emidio Cavalcanti; Jorge de Oliveira Echeimberg; Tassiane Cristina Morais; Blanca Elena Guerrero Daboin; Fernando Augusto Marinho dos Santos Figueira; Carlos Mendes Tavares; Luiz Carlos de Abreu (COVID)
Pernambuco, a northeastern Brazilian state, suffered significantly during the COVID-19 pandemic. The incidence, mortality, and fatality rates were incredibly high; these outcomes were a direct failure of the public health system to manage the COVID-19 pandemic. We developed an efficient method to analyze the trends in incidence, mortality, and lethality indicators of COVID-19 and the dynamics of their main determinants in the state of Pernambuco from March 2020 to March 2022. This was a time series ecological study. We calculated the lethality, mortality, and incidence rates with official and public data from the Health Department of this state. The effective reproduction number (Rt) was estimated, and then the periods were delimited, thus creating the efficiency model. Differences were considered significant when p < 0.05. We found 585,551 cases and 18,233 deaths from COVID-19. January 2022 was the month with the highest number of cases (6312) and, in May 2020, we recorded the highest number of deaths (149). Our method was efficient in analyzing periods of COVID-19, noting a contrast between the early and most recent periods, with the latter showing a stable number of new cases and patient deaths.